Unit Cost Analysis of Central Sterile Supply Department (CSSD) Services Using the Activity-Based Costing Method - Achmad Fauzi; Taufik Zulfikar; Rulia Rulia (Indonesian Journal of Global Health Research, 2026)
The Central Sterile Supply Department (CSSD) is a vital hospital support unit that ensures the availability of sterile medical instruments to support clinical services and prevent nosocomial infections. However, many hospitals in Indonesia, including Dr. Abdul Aziz General Hospital, Singkawang, have not established cost-based tariffs for CSSD services. This study aimed to calculate the unit cost of CSSD services at Dr. Abdul Aziz General Hospital, Singkawang, using the Activity-Based Costing (ABC) method. A descriptive qualitative study was conducted. Data were collected through observation, interviews with CSSD staff and management, and document review of financial and operational reports for the CSSD in 2024, specifically focusing on cost components, resource consumption, and activity volumes. Data Analysis used the Activity-Based Costing (ABC) method to meticulously trace overhead costs to services. This analysis followed six systematic steps: (1) identifying all cost components, (2) defining main CSSD activities, (3) determining appropriate cost drivers for each activity, (4) allocating total costs to each activity center, (5) calculating the unit cost per activity, and finally (6) determining the total cost for each instrument set sterilized. The total CSSD operational cost in 2024 was IDR 2,335,001,386, with a unit cost per sterilization cycle of IDR 2,470,901. Costs per instrument set were: major surgery set IDR 1,235,450; medium surgery set IDR 412,640; minor surgery set IDR 247,090; and single instrument IDR 123,545. Activity costs were dominated by sterilization (30%) and packing (25%). The ABC method produces more accurate cost calculations compared to traditional methods and can be used as a basis for tariff setting, cost control, and hospital financial planning. Future studies are recommended to expand the analysis to other hospital support units to benchmark efficiency and strengthen tariff policies.